dBrms1 Acts as a Positive Regulator of Notch Signaling in Drosophila Wing. - Zhang, Q.; Zhang, Y.; Wu, L.; Yang, Y.; Li, X.; Gao, L.; Hou, X.; Wu, Y.; Hou, G.; Li, Z.; Lin, X. (Journal of Genetics and Genomics [Yi chuan xue bao], 2014)
The highly conserved Notch signaling is precisely regulated at different steps in a series of developmental events. However, little is known about the regulation of Notch receptor at transcriptional level. Here, we demonstrate that dBrms1 is involved in regulating Notch signaling in Drosophila wing. We show that knockdown of dBrms1 by RNA interference (RNAi) in wing disc suppresses the expression of Notch signaling target genes wingless (wg), cut and Enhancer of split m8 [E(spl)m8]. Consistently, the levels of Wg and Cut are reduced in the dBrms1 mutant clones. Importantly, loss of dBrms1 leads to significant reduction of Notch proteins. Furthermore, depletion of dBrms1 results in apparent downregulation of Notch transcription in the wing disc. Moreover, we find that dBrms1 is functionally conserved with human Breast cancer metastasis suppressor 1 like (hBRMS1L) in the modulation of Notch signaling. Taken together, our data provide important insights into the biological function of dBrms1 in regulating Notch signaling.